The Concept of Istiṭā‘ah in the Rituals of Hajj: Ibn ‘Āshūr’s Perspective in Tafsīr al-Taḥrīr wa al-Tanwīr - Halimatus Sa'diyah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This paper aims to explore the concept of istiṭā‘ah in hajj according to Ibn ‘Āshūr ini his Tafsir al-Taḥrīr wa al-Tanwīr and implementation. This study employs a qualitative approach, specifically library research, utilizing written literature as the primary data source. The findings indicate that Ibn ‘Āshūr’s view Istiṭā‘ah encompasses both physical and financial capabilities Physical capability means that the individual must be in good health and able to undertake the journey for Hajj, while financial capability refers to having sufficient funds without neglecting the basic needs of their family. The implementation of this understanding allows for someone to delegate their Hajj to another person if they are suffering from a severe illness or have passed away. Conversely, performing Hajj is prohibited for those relying on loaned funds or still in debt, as these conditions are considered to not meet the Istiṭā‘ah requirement.